Maybe Next Month? Temperature Shocks, Climate Change, and Dynamic Adjustments in Birth Rates - Alan I. Barreca; Olivier Deschenes; Melanie Guldi (Institute for the Study of Labor (IZA), 2015)
Dynamic adjustments could be a useful strategy for mitigating the costs of acute environmental shocks when timing is not a strictly binding constraint. To investigate whether such adjustments could apply to fertility, we estimate the effects of temperature shocks on birth rates in the United States between 1931 and 2010. Our innovative approach allows for presumably random variation in the distribution of daily temperatures to affect birth rates up to 24 months into the future. We find that additional days above 80 °F cause a large decline in birth rates approximately 8 to 10 months later. The initial decline is followed by a partial rebound in births over the next few months implying that populations can mitigate the fertility cost of temperature shocks by shifting conception month. This dynamic adjustment helps explain the observed decline in birth rates during the spring and subsequent increase during the summer. The lack of a full rebound suggests that increased temperatures due to climate change may reduce population growth rates in the coming century. As an added cost, climate change will shift even more births to the summer months when third trimester exposure to dangerously high temperatures increases. Based on our analysis of historical changes in the temperature-fertility relationship, we conclude air conditioning could be used to substantially offset the fertility costs of climate change.
Keywords: I12; J13; Q54; 330; fertility; birth rates; seasonality; birth weight; temperature; climate change